The Effect of Participation in Recreational Activities on Students' Self-Confidence Levels before and after TEOG Exam - Yener Aksoy; Soner Çankaya; Yaşar Barut; Mert Çaloğlu; Mustafa Yasin Selçuk; Fatih Karakaş; Aydan Ermiş; Egemen Ermiş, (Revista de Psicología del Deporte (Journal of Sport Psychology), 2024)
The aim of this study is to investigate changes in the self-confidence levels of 8th grade students before and after the TEOG exam, a high school entrance exam administered by the Ministry of Education in Turkey. The exam, which evaluates students in core academic subjects, plays a crucial role in determining eligibility for Anatolian and Science High Schools, creating significant pressure on students due to its importance for their academic success and future career planning. The sample group of the research consists of 963 8th grade students. To collect data, the "Piers-Harris Self-Concept Scale" was used. The study analyzed whether the self-confidence scores of 8th grade students before and after the TEOG exam differed according to gender, number of siblings, and participation in physical activity, using repeated measures ANOVA. The results revealed that students who participated in recreational activities had higher self-confidence levels both before and after the exam compared to those who did not. Additionally, male students had higher self-confidence levels than female students both before and after the exam. The findings suggest that students' withdrawal from recreational and physical activities during exam periods negatively impacts their self-confidence. Therefore, it is important to encourage students to engage in physical and recreational activities to reduce their digital addiction during their free time and to help maintain their self-confidence at optimal levels.